2022
DOI: 10.1101/2022.12.17.520886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A monkeypox mRNA-lipid nanoparticle vaccine targeting virus binding, entry, and transmission drives protection against lethal orthopoxviral challenge

Abstract: Monkeypox virus (MPXV) caused a global outbreak in 2022, fueled by behaviorally-altered and enhanced human-to-human transmission. While smallpox vaccines were rapidly deployed to curb spread and disease among those at highest risk, breakthrough disease was noted after complete immunization. Given the imminent threat of additional zoonotic events as well as the viruses evolving ability to drive human-to-human transmission, there is an urgent need for the development of a MPXV-specific vaccine that is able to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…The MPXV has a set of highly conserved Orthopoxvirus surface proteins, which can be targeted to block the viral infection [ 6 ]. Among these surface proteins, MPXV A29 and M1 are involved in the cellular entry into the intracellular mature virion, while proteins B6 and A35 play important roles in the transmission on the surface of extracellular enveloped virion [ 10 ]. The poxvirus A35 protein is reported to be an important virulence factor of poxviruses.…”
Section: Introductionmentioning
confidence: 99%
“…The MPXV has a set of highly conserved Orthopoxvirus surface proteins, which can be targeted to block the viral infection [ 6 ]. Among these surface proteins, MPXV A29 and M1 are involved in the cellular entry into the intracellular mature virion, while proteins B6 and A35 play important roles in the transmission on the surface of extracellular enveloped virion [ 10 ]. The poxvirus A35 protein is reported to be an important virulence factor of poxviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Each has its own limitations such as severe skin side effects of live attenuated vaccine [14], weak immunogenicity of replication-deficient virus vaccines [24] and DNA vaccines [43], and long development cycle of recombinant protein technology [44]. Encouraged by the two new COVID-19 mRNA vaccines, some researchers have also tried to use mRNA technology to develop monkeypox vaccines, through the designing of multiple mRNAs that express a single or fused monkeypox antigen [45][46][47][48][49][50]. Some of those designs elicit potent immunogenicity but will face challenges in delivering multiple mRNAs during process development and manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction briefly works by conducting an isothermal MCDA reaction for the DNA templates followed by the lateral flow biosensor detection of the preamplification target sequences, with the optimal reaction temperature and time being 64 °C for 30 min. The detection tool developed in this study was shown to be effective and rapid [ 68 ]. Moreover, the efficient inhibition of cell-pathogen interactions to prevent infections is an urgent yet unsolved problem.…”
Section: Utilizing Nanomedicine Applications To Face Monkeypoxmentioning
confidence: 99%